The Latex Protein MLX56 from Mulberry (Morus multicaulis) Protects Plants against Insect Pests and Pathogens - Gai, Ying-Ping; Zhao, Ya-Nan; Zhao, Huai-Ning; Yuan, Chuan-Zhong; Yuan, Shuo-Shuo; Li, Shuo; Zhu, Bing-Sen; Ji, Xian-Ling (Frontiers in Plant Science, 2017)
Biotic stresses are major constraints limiting the leaf quality and productivity of mulberry. MLX56 is a unique chitin-binding protein isolated from Shin-Ichinose (Morus alba) latex that displays toxicity against lepidopteran caterpillars. In this study, the full-length cDNA encoding MLX56 was isolated from Husang 32 (M. multicaulis) and designated HMLX56. Amino acid sequence analysis and protein modelling of three MLX56 proteins showed that they were highly conserved among Morus species. Tissue expression pattern analysis showed that the HMLX56 gene was strongly expressed in mulberry bark and leaves but only slightly expressed in fruits. In addition, analysis of GUS expression indicated that the promoter of HMLX56 showed higher transcriptional activity along the vascular strands, and its activity can be regulated by various environmental factors. Like the MLX56 protein from M. alba, the HMLX56 protein showed toxicity to Plutella xylostella. Moreover, when the HMLX56 gene was ectopically expressed in Arabidopsis, the transgenic plants showed enhanced resistance to aphids, the fungal pathogen Botrytis cinerea and the bacterial pathogen Pseudomonas syringae pv. tomato DC3000. Our data suggest that the HMLX56 protein has a lectin-like molecular structure consisting of two hevein-like chitin-binding domains which provide not only chitin-binding activities but also other mechanisms of defence. The information provided here improves our understanding of the potential functions and defence mechanisms of MLX56 proteins, enabling in-depth functional analysis of latex exudates and perhaps facilitating mulberry genetic improvement in the future.